First record of Rhabdoblattella (Blaberidae, Epilamprinae) from China with descriptions of two new species - Wang, Zhenzhen; Yang, Rong; Wang, Zongqing (Zootaxa, 2017)
Two new species (Rhabdoblattella hainanensis sp. n. and Rhabdoblattella disparis sp. n.) from Hainan and Yunnan Provinces, China are described and illustrated, which extends the geographical distribution of Rhabdoblattella northward from Vietnam. Photographs and detailed morphological descriptions including the male genitalia of R. hainanensis sp. n. and R. disparis sp. n. are given. For comparison, the photos of habitus and male genitalia of a closely related species, R. annamensis (Hanitsch, 1927) are provided. A key to all species of Rhabdoblattella is provided.